APPLICATION OF BIOLOGICAL ADDITIVES-PREMIXES IN OSTRICH FARMING - Shakhlo, Babayeva; Shokhrukhbek, Kuziyev; Xursanali, Qutbiddinov; Muqaddas , Jalilova (International Journal on Orange Technologies, 2022)
This article talks about feeding ostriches, feed additives (Panaroot-98), premixes, and increasing productivity in Uzbekistan - as used in many sectors of agriculture.